Disabling Bioethics Futures - Dalrymple-Fraser, C. (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2024)
Relationships between disability and bioethics are often fraught, particularly when we are concerned with imagining possible futures. The futures imagined for disabled people are often futures without disabled people, utopias where disability has been cured, defeated, or overcome. How might we build better disability futures in a discipline so often committed to futures without disability? Here, I call for more creative inquiries into disability through research, representation, education, and engagement with disabled expertise.